Mycorrhizal Mediated Partitioning of Phosphorus: Ectomycorrhizal (Populus x canescens x Paxillus involutus) Potential to Exploit Simultaneously Organic and Mineral Phosphorus Sources - Schreider, Katharina; Hofmann, Diana; Boy, Jens; Andrino, Alberto; Fernandes Figueiredo, Aline; Sauheitl, Leopold; Guggenberger, Georg (Frontiers in Soil Science, 2022)
Many natural and anthropogenic soils are phosphorus (P) limited often due to larger P stocks sequestered in forms of low bioavailability. One of the strategies to overcome this shortage lies in the symbiosis of plants with mycorrhizal fungi, increasing the plant P uptake of these hardly accessible sources. However, little is known about mycorrhizal fungal mediated partitioning of differently available P forms, which could contribute to more efficient use of P by plants and, thereby, reduce competition for soil P. This study aimed to investigate the uptake of P from differently bioavailable P sources by ectomycorrhiza. For that, we conducted a rhizotrone study using Populus x canescens and its compatible ectomycorrhizal fungus Paxillus involutus. Four different P sources [ortho-phosphate (oP), adenosine monophosphate (AMP), hydroxyapatite (HAP), and oP bound to goethite (gP)] or only HAP as 1P control were supplied in separate compartments, where only the fungal partner had access to the P sources. The amount of the specific P sources was increased according to their decreasing bioavailability. In order to distinguish between the P sources, we applied 33P to track its incorporation in plants by a non-destructive analysis via digital autoradiography. Our results show that an ectomycorrhizal plant is able to utilize all provided P sources via its mycorrhizal fungal associate. The acquisition timing was determined by the most bioavailable P sources, with oP and AMP over HAP and gP, and a mixed P pool over a single P source. In contrast, the magnitude was defined by the by the amount of supplied P source provision of additional nitrogen, hence AMP over oP and gP, as well as by P source complexity, with gP as the least favorable P form. Nevertheless, the results of the present study provide evidence that an ectomycorrhiza has the potential to occupy fundamental niches of various P sources differing in their bioavailability, indicating that being a generalist in P nutrition can facilitate adaptation to various nutritional settings in soil.